Rainwater harvesting system as a strategy for adaptation on climate change: a review - Ruiz Martínez, Heidy Gabriela (2022)
In the face of increasing water scarcity aggravated by climate change, the rainwater harvesting system is a technique that increases the water supply for various purposes. The objective of this research is to analyse the recent literature published on the rainwater collection system, for which the systematic review method was used. The main form of rainwater catchment are roofs, but the material used is important because it can affect the quality of the water. Some physicochemical parameters of rainwater may be within the standards for human consumption, but it is contaminated by pathogenic microorganisms, which represents a risk to public health if it is consumed without prior treatment, so it is mainly used for irrigation and flushing toilets. However, this system has been implemented mainly in rural areas to satisfy their basic needs, including human consumption, because these places do not have access to the central drinking water system. Given this scenario, treatment technologies are being developed that are easy to operate and maintain, such as solar disinfection and filtration for drinking water purposes. This study provides a global overview progress of research related to the rainwater harvesting system.